Application of Transcriptome Analysis for the Exploration of the Mechanism of Methionine Promoting the Synthesis of Cephalosporin C in Acremonium chrysogenum by Employing a Chemically Defined Medium - Yifan Li; Zhen Chen; Wei Hong; Tao Feng; Xiwei Tian; Ju Chu (Fermentation)
To better analyze the biosynthesis mechanism of cephalosporin C (CPC) in Acremonium chrysogenum, single-factor omission experiments and Plackett–Burman (PB) experimental design were employed to identify key components in the chemically defined medium. Response surface methodology (RSM) was then applied to optimize the concentrations of critical factors, achieving a final CPC titer of 4.70 g/L, which reached 59.54% of the titer obtained with complex medium. Methionine was identified as the most significant amino acid influencing CPC production during medium optimization. On the basis of these findings, transcriptomic analysis was conducted to elucidate the regulatory role of methionine. The results revealed that methionine enhances CPC biosynthesis by upregulating cysteine metabolism-related genes and activating primary metabolic pathways to supply precursors and energy for secondary metabolism. Additionally, methionine promoted hyphal swelling and arthrospore formation, leading to the upregulated expression of genes in CPC biosynthetic gene clusters. By integrating medium optimization with transcriptomic analysis, we provided more reliable insights into the regulatory role of methionine in A. chrysogenum growth and CPC biosynthesis using a chemically defined medium, offering valuable guidance for fermentation process optimization and subsequent metabolic engineering strategies.